Analisis Naratif Product Placement Daihatsu dalam Web Series Mulih - Pahlevi, Muhammad Haykal; Utamidewi, Wahyu; Kusumaningrum, Rastri (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The current information age provides various ways that are used by certain parties in marketing their products, one of which is by using video media to create Web series. This study aims to examine the four-episode Mulih web series which airs on the Daihatsu Sahabatku channel. In this web series, several Daihatsu product lines appear as vehicles that support the narrative of the actors. This study dissects Product Placement practices conducted by PT. Astra Daihatsu Motor with the concept of Product Placement Dimension namely Visual, Auditory and Plot Connection and Elaboration Likelihood Model. This study uses narrative analysis and conducts interviews with some viewers of the Mulih Web Series. The results show that the Plot Connection dimension dominates the Web Series with a storyline that focuses on Daihatsu vehicles. Apart from that, the audience also indicated that there was a difference in the elaboration resulting from watching this Web Series. Of the four informants, there were at least two informants who leaned towards the central path while the other two leaned towards the peripheral path. The formation of this elaboration is based on the background or motivation of the audience and the ability to think what they can do. Daihatsu seems to be trying to give the audience subtle hints without bringing up the technical aspects, but more about how the story is told. Keywords: Web Series; Product Placements; Elaboration Likelihood Model; Narrative Analysis